2015
DOI: 10.1002/elps.201400480
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as a model for the study of high frequency dielectrophoresis

Abstract: Liposomes were used as a physical model to study the dielectrophoretic response of single-shelled particles at high frequencies. For a typical particle, the single-shelled theoretical model predicts a lower cross-over frequency that depends upon the dielectric properties of the shell and an upper crossover frequency that depends upon the dielectric properties of the interior. Dried liposomes were rehydrated in media with conductivity ranging from 100 to 2000 μS/cm. The high frequency dielectrophoresis response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Peterlin et al 161 studied electro-deformation in phospholipid vesicles using AC electric field and correlated the experimentally observed prolate-tooblate transition frequency ranges with previous literature. 162 Hadady et al 163 used liposomes to study the single-shell DEP model at high frequencies in various conductivity media. They observed an upper crossover frequency in the range of 9−60 MHz and reported a linear dependency of upper crossover frequency on the interior conductivity of liposomes, in agreement with the single-shell DEP theoretical model.…”
Section: ■ Technical Realization Platforms For Depmentioning
confidence: 99%
“…Peterlin et al 161 studied electro-deformation in phospholipid vesicles using AC electric field and correlated the experimentally observed prolate-tooblate transition frequency ranges with previous literature. 162 Hadady et al 163 used liposomes to study the single-shell DEP model at high frequencies in various conductivity media. They observed an upper crossover frequency in the range of 9−60 MHz and reported a linear dependency of upper crossover frequency on the interior conductivity of liposomes, in agreement with the single-shell DEP theoretical model.…”
Section: ■ Technical Realization Platforms For Depmentioning
confidence: 99%
“…Lamellarity, determines the stability of liposomes' preparations [10], the amount of lipophilic drugs that can be encapsulated, the kinetics of their release [4] and the fate of liposomes when interacting with cells [7]. Moreover, it also determines the overall mechanical [11] and dielectric [12] properties of the liposomes, which are relevant in their interaction with cells [13,14] or in their electrokinetic manipulation [15]. Finally, when used as cell model systems, strict control of the lamellarity is a pre-requisite [6].…”
Section: Introductionmentioning
confidence: 99%
“…low electric field [33]. This has led to research in designing effective non-uniform electric fields by judicious design of electrodes, often in microfluidic/nanofluidic chips by microfabrication techniques [36,16,35] has gained prominence.Giant Unilamellar Vesicles (Liposomes) (GUVs) have emerged as a very reliable bio-memetic system and has been used to understand the DEP response of cells [37,38]. Unlike biological cells, there are very few experimental [37,39,40] and theoretical [41] investigations on the DEP of vesicles .…”
mentioning
confidence: 99%
“…Korlach et al, [42] created a 3D electric field cage to study vesicle deformation and electro-rotation by trapping a vesicle using optical tweezers. Studies on the modification of the electrical properties of GUVs to serve them as test particle for DEP study [43], high-frequency DEP response of vesicles to estimate upper and lower crossover frequency at different interior conductivity and membrane electric properties [38] and DEP studies on surface-modified liposomes in AC fields [39], have also been reported . A vesicle under non-uniform, axisymmetric quadrupole electric field, not only exhibits dielectrophoresis, but can also deform.…”
mentioning
confidence: 99%
See 1 more Smart Citation